(untitled) (American Journal of Interdisciplinary Research and Innovation, 2023)
This study aimed the following: (1) develop a Student-based Interactive Physics Activity (SIPA) app game and (2) determine the conceptual change in Force and Motion. The study employed a developmental research design with three phases: input, process, and output. The Physics activity was intended for classroom instruction, especially for grade 9 students. The evaluation of the SIPA app game was done by the in-service Physics teachers using the App Checklist for Educators (ACE). The readability of the Physics activity was administered using Flesch-Kincaid Test. The result of the evaluation was the basis for the enhancement of the app game and learning activity. The SIPA app game was commendable regarding student interest, design features, connection to curriculum, instruction features, and rating and review. The modified Physics activity was ascertained appropriate for Grade 9 learners. The leaners improved; thus, the SIPA app game was proven workable.